Comparison of clinicians' and advanced cancer patients' estimates of survival. Issue 4 (1st December 2015) - Gwilliam, B; Keeley, V; Todd, C; Gittens, M; Roberts, C; Kelly, L; Barclay, S; Stone, P
Abstract : Abstract: Aims: To determine whether doctors, nurses or the multi-professional team (MPT) are better at prognosticating in advanced cancer. To determine which clinician factors influence prognostic accuracy. To investigate patients' views about receiving prognostic information and to evaluate the accuracy of their own estimates. Methods: As part of a large prospective multi-centre study to develop a novel prognostic scoring system for patients with advanced cancer, clinicians were asked to estimate whether patients were expected to live for 'days', 'weeks' or 'months+'. Patients were asked whether and how they would wish to receive prognostic information and whether they would be willing/able to estimate their own prognosis. Survival was calculated from date of study entry. Prognostic accuracy of different groups was compared using linear weighted κ (LWK). Results: 1018 patients with advanced cancer were studied; 127 doctors, 281 nurses and 290 patients provided 829, 954 and 290 prognostic estimates respectively. MPT estimates were available for 987 patients. LWK varied between 0.14 (patients) and 0.46 (MPT). Patients' estimates were significantly worse than doctors', nurses' or MPT estimates (all p<0.001). Nurses' estimates were significantly worse than the MPT estimate (p=0.007). No clinician factors (age, gender, experience or grade) were consistently associated with better prognostic accuracy. Most patients (61.4%) wanted to know their prognosis of whom 48% wanted to know it 'approximately' and 52% wanted to know 'exactly'. Conclusion: Most patients wish to know their prognosis. Clinicians' predictions are inaccurate and patients' predictions are significantly worse. MPT estimates are the most accurate.